The Women : A Family Story - Bate, Kerry William (Book collections on Project MUSE., 2016)
"A singular narrative woven from the biographies of four generations of women in southwestern Utah. This book takes a provocative and unapologetic look at the lives of four generations of women from 1816 to 1949, who faced all that men, environment, and God could throw at them. It's the story of failings and triumph in a world that often valued women cheaply, dismissed them easily, and granted nothing cheerily. Though their stories are informed by Utah and Mormon history, their lives represent the experiences of many women of their era. They also provide a personal look at the effects of technological and societal changes in the nineteenth and early twentieth centuries. While all four women moved within the lower spheres of economic status, several of them played important roles in their towns in southwestern Utah. Their stories share the rich social history of these communities and their interactions with other town members. With humor and detail, Kerry Bate reveals the women's struggles to nurture their families and survive, the value they found in joining forces, and their sometimes subtle insubordination against the rules of men"--